The Roeper School
Approx. 5 p.
Keywords: How can we design schools that energetically promote intellectual development while also attending to the social, emotional, and ethical growth of students? In today’s frenzied climate of accountability driven school reform it is difficult to establish anything more than achievement of superficial knowledge and skill. Fortunately, there is a vibrant example of holistic, student-centered education that engenders dynamic, multidimensional student growth. The Roeper School enables students to develop strong intrinsic motivation as they discover aspirations and develop talents consistent with those aspirations. Simultaneously, from a very young age students take considerable responsibility for their own actions and for the processes that go on in their school. Following the Roeper philosophy each student generates a long-term sense of purposeful direction, a strong sense of intrapersonal awareness, impressive creative and critical thinking skills, and a finely tuned sense of ethical responsibility. Upon graduation Roeper students are well prepared to find or create highly productive niches in the world of work and rewarding personal lives while serving as mature, ethical citizens of a complex, 21st-century, globalized society. This book includes descriptions of the multidimensional education the Roeper School provides. The perspectives in the volume are diverse, coming from leading researchers and theorists in the field of gifted education as well as teachers, administrators, alumni, and current students from the school itself. Overall, the book provides a beacon of hope for 21st-century education.